Hubungan Supervisi Infection Prevention and Control Nurse (IPCN) dengan Kepatuhan Penggunaan Alat Pelindung Diri (APD) di Ruang Rawat Inap RS Grha Permata Ibu Depok Tahun 2025 - Sugiarti, Astri; Inas Syabanasyah; Solehudin Solehudin (PPNI UNIMMAN, 2026)
Healthcare-Associated Infections (HAIs) remain a major global challenge in healthcare services, contributing significantly to increased morbidity, mortality, and healthcare costs. Nurses’ compliance with the use of Personal Protective Equipment (PPE) is a critical component in infection prevention and control programs. Supervision by Infection Prevention and Control Nurses (IPCNs) is considered a key factor in improving compliance. This study aimed to analyze the relationship between IPCN supervision and nurses’ compliance with PPE usage in inpatient wards at Grha Permata Ibu Hospital, Depok, in 2025. This study employed a quantitative approach using a correlational analytic design with a cross-sectional method. The population consisted of all 56 nurses working in four inpatient wards, and total sampling was applied. Data were collected using a structured IPCN supervision questionnaire and direct observation checklists of PPE compliance. Data analysis included univariate and bivariate analysis using the Chi-square test. The results revealed that most respondents perceived IPCN supervision as moderate (58.9%), while the majority demonstrated compliance with PPE usage (62.5%). Bivariate analysis indicated a statistically significant relationship between IPCN supervision and PPE compliance (p = 0.001). Nurses receiving high-level IPCN supervision were 33.85 times more likely to comply with PPE usage compared to those receiving moderate supervision. In conclusion, IPCN supervision plays a crucial role in enhancing nurses’ compliance with PPE usage. Strengthening IPCN supervisory functions through structured monitoring, continuous education, and consistent evaluation is strongly recommended to improve patient and healthcare worker safety and to reduce the incidence of HAIs in hospital settings.